Clinical and statistical considerations in personalized medicine - Carini, Claudio; Menon, Sandeep M.; Chang, Mark (Boca Raton : CRC Press/Taylor & Francis Group, 2014)
'Personalized medicine has the potential to change the way we think about, identify, and manage health problems. In the pharmaceutical industry, it is already having an exciting impact on both clinical research and patient care. This impact will continue to grow as our understanding and technologies improve. With contributions from well-known industry leaders in clinical development, this book covers the practical aspects of personalized medicine, focusing on issues that have direct application in the industry. Topics include designs for targeted therapy, adaptive designs, evidence-based adaptive statistical decisions, and design strategies for maximizing the efficiency of clinical oncology'--
'Preface The successful utilization of biomarkers in clinical development and, indeed, realization of personalized medicine require a close collaboration among different stakeholders: clinicians, biostatisticians, regulators, commercial colleagues, and so on. For this reason, we invited experts from different fields of expertise to address the opportunities and challenges, and discuss recent advancements related to biomarkers and their translation into clinical development. The first four chapters discuss biomarker development from a clinical perspective ranging from introduction to biomarkers to recent advances in RNAi screens, epigenetics, and rare disease as targets for personalized medicine approaches. Chapters 5 through 10 are devoted to considerations from a statistical perspective, and the last chapter addresses the regulatory issues in biomarker utilization. A biomarker is a characteristic that can be objectively measured and evaluated as an indicator of a physiological as well as pathological process or response to a therapeutic intervention. Although there is nothing new about biomarkers such as glucose for diabetes and blood pressure for hypertension, the current focus on molecular biomarkers has taken the center stage in the development of molecular medicine. Molecular diagnostic technologies have enabled the discovery of molecular biomarkers and are assisting in the definition of the pathogenic mechanism of diseases. Biomarkers represent the basis of the development of diagnostic assays as well as the target for drug discovery. Biomarkers can help monitoring drugs effect in clinical trials as well as in clinical practice'--
1. Biomarkers for drug development : the time is now! / Claudio Carini and Attila Seyhan -- 2. RNAi screens : triumphs and tribulations / Attila Seyhan and Claudio Carini -- 3. Current advances in epigenetics / Ewan Hunter and Alexandre Akoulitchev -- 4. Biomarkers and precision medicine : the case of rare diseases / Candida Fratazzi and Claudio Carini -- 5. Biomarker-informed adaptive design / Jing Wang, Mark Chang, and Sandeep Menon -- 6. Fitting the dose : adaptive staggered dose design / Joseph Wu, Sandeep Menon, and Mark Chang -- 7. Evidence-based adaptive statistical decision and design strategies for maximizing the efficiency of clinical oncology development programs with predictive biomarkers / Cong Chen and Robert A. Beckman -- 8. Biomarker identification in clinical trials / Ilya Lipkovich and Alex Dmitrienko -- 9. Multiplicity in pharmacogenomics / Lingyun Liu, Fredrick Immermann, and Sandeep Menon -- 10. Patient-reported outcomes in personalized medicine / Demissie Alemayehu and Joseph C. Cappelleri -- 11. Regulatory issues in use of biomarkers in drug development / Aloka G. Chakravarty.
Includes bibliographical references and index.
Keywords: Pharmacogenetics -- statistics & numerical data; Biological Markers; Drug Discovery -- statistics & numerical data; MATHEMATICS -- Probability & Statistics -- General; MEDICAL -- Internal Medicine; MEDICAL -- Pharmacology